Expert panel on cost analysis of atrial fibrillation - FAK, ALİ SERDAR (TURKISH SOC CARDIOLOGY, 2013)
Objective: To estimate total cost of atrial fibrillation (AF) management concerning acute coronary syndrome, heart failure, stroke and drug related adverse events with respect to clinical practice and available guidelines. Methods: This cost analysis study was based on identification of total costs related to management of acute coronary syndrome, heart failure, stroke and the drug related adverse events in patients with AF based on standardized questionnaire forms filled by experts according to their daily clinical practice and also to ACCF/AHA/ESC guidelines. Total cost included cost items related to treatment, healthcare resources utilization, and diagnostic test and consultations. Results: The yearly cost of acute coronary syndrome per patient was 5.478.43 TL according to expert's view reflecting real clinical practice whereas it was 11.319.44 TL when calculation was based on recommendations in the guidelines. The average total cost of heart failure was 4.523.74 TL according to expert's view whereas it was 2.925.86 TL based on guidelines. The average total cost of stroke was 5.719.25 TL according to expert's view but 7.931.18 TL based on guidelines. Among drug related adverse events, only those related to cardiac adverse events were estimated to be higher according to expert view as compared to guideline recommendations (288.65 vs. 150.99 TL). Conclusions: Reflecting the treatment algorithms in the management of AF and related adverse events, our findings seem to emphasize the extra burden on health economics posed by patients suffering from the uncontrolled disease. (Anadolu Kardiyol Derg 2013; 13: 26-38)
Keywords: Atrial fibrillation; acute coronary syndrome; heart failure; stroke; adverse events; cost analysis; ASSOCIATION TASK-FORCE; ELEVATION MYOCARDIAL-INFARCTION; GUIDELINES WRITING COMMITTEE; KEY DATA ELEMENTS; QUALITY-OF-LIFE; AMERICAN-COLLEGE; EUROPEAN-SOCIETY; CARDIOVASCULAR ANGIOGRAPHY; PULMONARY REHABILITATION; CARDIOLOGY COMMITTEE